1991
DOI: 10.1037/0022-3514.61.6.992
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in ego defenses in adolescence: Sex roles as one way to understand the differences.

Abstract: Gender differences in ego defenses were hypothesized in adolescence, with greater internalization by girls and greater externalization by boys. Through the inclusion of sex role constructs (masculinity and feminity, agency and communion, and passivity-dependency), relational models as well as psychoanalytic theory were investigated as bases for sex differences. The Berm Sex Role Inventory and the Defense Mechanism Inventory were administered to 66 high school students (31 boys and 25 girls), ages 14-19. As exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
1
30
1
2
Order By: Relevance
“…This is consistent with findings made by Watson and Sinha [25] and La Cour [24]. Females are generally more emotionally labile as compared to their male counterparts who are better at splitting emotional components from their thoughts [28], as shown by higher means for Isolation in men in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with findings made by Watson and Sinha [25] and La Cour [24]. Females are generally more emotionally labile as compared to their male counterparts who are better at splitting emotional components from their thoughts [28], as shown by higher means for Isolation in men in our study.…”
Section: Discussionsupporting
confidence: 93%
“…The positing of gender differences in defenses on the basis of classical psychoanalytic theory [1] has generally been supported in prior investigations, which state that women tend to use internalizing defenses such as Introversion, and men are more likely to employ externalizing ones [28-30] such as Projection and Aggression [30-32]. …”
Section: Discussionmentioning
confidence: 99%
“…Downloaded by [University of Nebraska, Lincoln] at 12:57 13 October 2014 ACTUAL AND PERCEIVED PEER ACCEPTANCE An important consideration in testing these models is whether the prediction of dysphoria from actual and perceived acceptance differs by sex. Several studies reported that low peer acceptance was more strongly related to dysphoria for girls than boys (Cole, 1991b;Kupersmidt & Patterson, 1991;Morison & Masten, 1991), a finding that fits with the view that girls place more importance on social relationships (e.g., Allgood-Merton, Lewinsohn, & Hops, 1990;Levit, 1991). In contrast to these results, others found that peer acceptance predicted dysphoria better for boys than girls (Block, Gjerde, & Block, 1991;Girgus, Nolen-Hoeksema, & Seligman, 1989).…”
Section: This Studymentioning
confidence: 70%
“…These findings suggest that defense use is moderated by sex role, and thus by social learning (Levit, 1991). They also suggest that females who direct negative affect inwardly are more prone to psychological difficulties, especially depression, as found by Gjerde, Block, and Block (1988).…”
Section: Discussionmentioning
confidence: 81%